2014
DOI: 10.1016/j.joca.2014.02.814
|View full text |Cite
|
Sign up to set email alerts
|

Falls associated with knee instability in people with knee osteoarthritis: biomechanical risk factors and pain

Abstract: ¼ 0.67, p < 0.01). Specifically, less knee pain, stronger plantarflexors, quadriceps and hamstrings, greater knee flexion range of motion, and greater APA velocity were related to better scores on the CB&M. Conclusions: Dynamic balance and mobility were related to a number of modifiable factors as eccentric plantarflexor, quadriceps, and hamstrings strength, knee joint range of motion and APA velocity. Given the considerable personal and economic burden of falls and the strong link to dynamic balance and mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, it is not only professional athletes at risk of these injuries, as Loes, Dahlstedt, and Thomée [2] reported that knee injury accounted for 15% to 50% of injuries related to 12 different sports during a longitudinal seven year trial of recreational male and female exercisers. Knee instability is a problem affecting both young and old individuals, as those aged over 65 years have been reported to suffer from one to three incidences of falls due to several factors, including self-reported knee instability [3]. It affects a varied population, including professional athletes [4,5], older adults, and recreational exercisers [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not only professional athletes at risk of these injuries, as Loes, Dahlstedt, and Thomée [2] reported that knee injury accounted for 15% to 50% of injuries related to 12 different sports during a longitudinal seven year trial of recreational male and female exercisers. Knee instability is a problem affecting both young and old individuals, as those aged over 65 years have been reported to suffer from one to three incidences of falls due to several factors, including self-reported knee instability [3]. It affects a varied population, including professional athletes [4,5], older adults, and recreational exercisers [6].…”
Section: Introductionmentioning
confidence: 99%
“…It affects a varied population, including professional athletes [4,5], older adults, and recreational exercisers [6]. The impact of knee instability can be severe, and may lead to an increased risk of falls [3] and a long period of rehabilitation [7]. These consequences of knee instability increase the cost to health care systems [8,9].…”
Section: Introductionmentioning
confidence: 99%